2020
DOI: 10.34172/jlms.2020.35
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Laser Effects on Skin Rejuvenation

Abstract: Laser skin resurfacing has changed the approach of facial skin rejuvenation over the past decade. This article evaluates the laser effects on skin rejuvenation by the assessment of laser characteristics and histological and molecular changes, accompanied by the expression of proteins during and after laser-assisted rejuvenation of skin. It is important to note that different layers of skin with different cells are normally exposed to the sun’s UV radiation which is the most likely factor in aging and damaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 88 publications
(80 reference statements)
0
30
0
Order By: Relevance
“…Later, it was discovered that 1064-QSNYL can cause inflammation in the damaged local area, thereby starting the tissue self-repair process, inducing the degeneration of dermal collagen, stimulating the proliferation of fibroblasts, increasing collagen regeneration, and increasing skin water content to achieve the effect of skin rejuvenation. [21][22][23] the senescence of epidermal keratinocytes by inhibiting the expression of SATB1. 24 Li et al 25 shown that lncRNA RP11-670E13.6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, it was discovered that 1064-QSNYL can cause inflammation in the damaged local area, thereby starting the tissue self-repair process, inducing the degeneration of dermal collagen, stimulating the proliferation of fibroblasts, increasing collagen regeneration, and increasing skin water content to achieve the effect of skin rejuvenation. [21][22][23] the senescence of epidermal keratinocytes by inhibiting the expression of SATB1. 24 Li et al 25 shown that lncRNA RP11-670E13.6…”
Section: Discussionmentioning
confidence: 99%
“…Goldberg first used 1064‐QSNYL for wrinkle removal in 1997, and proposed the concept of "laser nondamage skin rejuvenation technology" for the first time. Later, it was discovered that 1064‐QSNYL can cause inflammation in the damaged local area, thereby starting the tissue self‐repair process, inducing the degeneration of dermal collagen, stimulating the proliferation of fibroblasts, increasing collagen regeneration, and increasing skin water content to achieve the effect of skin rejuvenation 21‐23 . 1064‐QSNYL has fully demonstrated its effectiveness and advantages in the treatment of skin aging.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modalities are of current use for facial rejuvenation purpose, as previously discussed 3–10 . Fractional nonablative lasers are considered safer modalities compared to the ablative ones as they demonstrate a lower pain levels, better side effect profile and a shorter downtime 10–16,24 …”
Section: Discussionmentioning
confidence: 99%
“…Energy‐based devices such as: intense pulsed light (IPL), radiofrequency, and lasers are of growing use for this purpose in recent years 7–9 . The ablative lasers (the 10 600‐nm CO 2 laser and the 2940‐nm Erbium:YAG laser) are of more common use; however, they are associated with significant adverse effects (dyspigmentation, edema, and erythema), risk for infections, and significant postprocedure downtime 10–17 . Nonablative lasers with a much shorter postprocedure downtime have heterogeneous efficacy in the treatment of facial rhytids and skin rejuvenation 10–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation